The Effect of Sodium Bicarbonate (NaHCO3) and Bamboo Shoot Flour (Dendrocalamos Asper) addition on the Quality of Sweet Potato (Manihot Utilisima) Crackers - Khairiah Nur; Rahmat Afrizal; Yuslinaini Yuslinaini (Universitas Serambi Mekkah, 2019)
Bamboo shoots are bamboo plants that have many health benefits because they are rich in Food fiber and potassium. Making crackers with the addition of bamboo shoot flour is one way of using bamboo shoots in food. The purpose of this study was to see the effect of adding sodium bicarbonate, adding bamboo shoot flour and the interaction of adding sodium bicarbonate and bamboo shoot flour to the quality of cassava crackers. This study followed a completely randomized design with 2 levels with 3 levels namely bamboo shoot flour (10%, 20% and 30%) and sodium bicarbonat (0.01%, 0.02% and 0.03%). The results showed that the best treatment of water content was obtained at 0.01% NaHCO3 and 20% bamboo shoot flour at 12.26%. The best ash content was 10% bamboo shoot flour and 0.03% NaHCO3 2.26%. The color and taste organoleptic tests on bamboo shoot flour and NaHCO3 were 2.33 (disliked) in color and 2.47 (disliked), respectively